Pengembangan Bahan Ajar Bioenterpreneurship Berbasis Creative Problem Solving Untuk Melatih Keterampilan Ekoliterasi Calon Guru Biologi - Nawawi Nawawi; Rio Wardhani (Universitas Muhammadiyah Prof. Dr. Hamka, 2023)
Background: Fierce competition requires graduate students from IKIP PGRI Pontianak to have pedagogical abilities, soft skills, hard skills, and interpersonal skills that can be used in the world of work. The research will aim to develop Bio-entrepreneurship teaching materials based on Creative Problem Solving to train eco-literation skills. Methods: The research method uses research and development intending to produce a new product that refers to the ADDIE development model, which includes five stages, namely, Analysis, Design, Development, Implementation, and Evaluation. The research was carried out in the Biology Education Study Program; before the product was given to experts, researchers tested Bio-entrepreneurship teaching materials based on Creative Problem Solving to train eco-literation skills. Results: The next validation stage will involve material and media experts, and research will involve students taking the Bio-entrepreneurship course in the Biology Education Study Program, which was previously given a pre-test and post-test. The research instruments used are expert validation sheets, product assessments, questionnaires, and eco-literation tests. Data analysis was carried out on the results of expert validation, student responses, and student learning outcomes using SPSS. Bio-entrepreneurship Teaching Materials Based on Creative Problem Solving meet the criteria of validity and practicality based on the results of assessments from media experts and material experts, based on the calculation of N-gains, a value of 61,267 or 61.27% is included in the category of quite effective. Conclusions: Bio-entrepreneurship Teaching Materials Based on Creative Problem Solving meet correct categorizations and are adequate for learning.